Development of Fructuweb “A Learning Website of Banten’s Exotic Fruits” to Support Local Potential-Based Learning in Digital Era - Marianingsih, Pipit; Putri, Ratu Sofie Azkia; Aliani, Dini; Kamila, Alifia Tasya; Usman, Usman; Amelia, Evi; Hodijah, Siti Romlah Noer; Leksono, Suroso Mukti (Jurnal Penelitian dan Pembelajaran IPA, 2021)
Teaching-learning in the 21st-century is influenced by technological advances, such as the use of online media. In addition, based on Indonesia’s curriculum requirements, teaching-learning has to utilize the local potential of the environment. This study aims to develop a Fructuweb, a learning website with Banten’s exotic fruits as content to support local potential-based learning in the digital era. A 3D research and development methodology was used comprise of define, design, and develop. The subjects for expert validation were five lecturers, and for individually user response tests were four teachers and fifteen students of 10th-grade representatives from senior high school in Serang city and Lebak district, Banten Province. Descriptive analysis were carried out to identify learning process and media need in schools at Banten, also to validate the feasibility of the website. The expert validation result has an average value of 95.1% for the content material aspect of Fructuweb and 92.7% for the media aspect;  as for the user response (student and teacher) was 93.4%. These results indicated that the Fructuweb is very feasible to use as an online learning source.